Sveta brata Ciril in Metod kot zavetnika Evrope - Pivec, Franci (Edinost in dialog, 2013)
The starting point of the article is Slomšek's foundation of the Ss. Cyril and Methodius prayer fraternity, which should have facilitated the unification of Catholics and Orthodox Catholics. By doing so, he brought attention to the Slav apostles who, before and after that, went through different forms of instrumentalisation that was opposed to their beliefs. Even when they were still alive they were victims of political interests, which also happened in later times, often in the form of a nationalist appropriation of their ideas. Their proclamation as the Patrons of Europe is justified, but at the same time requires a critical approach towards the historical distortion of their acts. In this respect, a good example is provided by the Slovene experts on these two missionaries, especially A. M. Slomšek and F. Grivec, who understood the transnational significance of Cyril and Methodius. On these grounds, we could make a significant contribution towards the European memory, which has been neglected so far. At the same time, it would be useful to take Halbwachs" and Assmanns theoretical approach of "places of memory" and figures of memory" into account. But mostly one would have to take Slomšek's advice that the ideas of Ss. Cyril and Methodius cannot be successful if political and national interests interfere, with the intention of one side overruling the other.
Keywords: Cyrillus, svetnik, 826-869; Methodius, svetnik, 815-885; svetniki; zavetniki; Europe; Evropa; krščanstvo; Christianity